The importance of intellectuals in the formation of ideological hegemony - Е.К. Қожбанхан; А.Д. Калдыбекова (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
This article discusses the theory of “gli intellettuali” or “intellectuals”, which occupies a very important place in the philosophy of the Italian philosopher Antonio Gramsci using the method of critical evaluation. In more detail, in the context of such concepts as the historical block and the philosophy of praxis, the theory of intellectuals in the works of Gramsci and the specifics of its use are analyzed. In addition, it considers the arguments: why and how the theory of intellectuals Gramsci differs from the classical elitist concept of intellectuals who dominated political philosophy from Plato to Hegel. And also investigated the difference between organic and traditional intellectuals.